Strategic Leadership, Organizational Innovativeness and the Firm Supply Performance: The Mediating Role of Information Technology Capability - Pimploi Tirastittam; Kittisak Jermsittiparsert; Phutthiwat Waiyawuththanapoom; Wissawa Aunyawong (International Journal of Supply Chain Management, 2020)
The main objective of the current study is to examine the impact of the strategic leadership, and the organizational innovation on the firm supply performance. Additionally, the study has examined the mediating role information technology capability in the relationship between the strategic leadership and firm supply performance, and between the organizational innovation and firm supply performance. The study has used the resource-based view, the theory is useful for IT research through resource attributes, which facilitates the relationship between IT resources and non-IT resources, since the resource-based theory establishes a clear link between resources and sustained competitive advantage. It is generally agreed upon by information system scholars that IT capabilities can act as key enablers of higher order organizational capabilities or interact with other. The study has used the SEM-PLS to examine the relationship between and among the variables. The response rate of the current study is 44.7 percent. The results have highlighted that the relationship between strategic leadership, organizational innovativeness and firm supply performance are significant. Results from the study give support to the key theoretical propositions. Precisely, the present study has succeeded in answering all the research questions as well as the objectives despite some of limitations. While there have been, numerous studies investigating the factors that affect strategy implementation, however, the current study addressed the theoretical gap by incorporating IT capability as a significant mediating variable for strategic leadership.